2014
DOI: 10.1159/000366418
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Glue Does Not Improve Healing of Gastrointestinal Anastomoses: A Systematic Review

Abstract: Background/Aim: Anastomotic leakage remains a frequent and serious complication in gastrointestinal surgery. In order to reduce its incidence, several clinical and experimental studies on anastomotic sealing have been performed. In a number of these studies, the sealing material has been fibrin glue (FG), and the results in individual studies have been varying. The positive effect of anastomotic sealing with FG might be due to the mechanical/physical properties, the increased healing of the anastomoses or both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 76 publications
1
38
0
Order By: Relevance
“…In the second study the usage of the same material on a colonic anastomosis showed notable reduction of anastomotic leakage 47 . However, when it comes to clinical use of this material, the fibrin glue does not seem to promote healing as the same authors stated in their review article including 28 studies, only 7 of which revealed a positive effect of the glue 48 . Recently, a clinical study was designed to determine the effect of TachoSil patch in human patients 12 .…”
Section: Discussionmentioning
confidence: 84%
“…In the second study the usage of the same material on a colonic anastomosis showed notable reduction of anastomotic leakage 47 . However, when it comes to clinical use of this material, the fibrin glue does not seem to promote healing as the same authors stated in their review article including 28 studies, only 7 of which revealed a positive effect of the glue 48 . Recently, a clinical study was designed to determine the effect of TachoSil patch in human patients 12 .…”
Section: Discussionmentioning
confidence: 84%
“…In addition, a previous systematic review produced by the same study group, has revealed that application of fibrin sealants on colonic defects is promising (24). However, the most recent systematic review relevant to this field failed to show a clear benefit from the use of fibrin glue on colorectal anastomoses (25). in vivo 34: 659-665 (2020) 662 Table II.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies regarding the efficacy of medical adhesives are equivocal, and in recent reviews, the ambiguity of the effectiveness and practical usefulness of medical adhesives has been emphasized; the positive effect can be attributed to strengthening the anastomosis rather than influencing healing [54], which has been confirmed by pathology studies of anastomoses in experimental models [54]. In the literature, there are reports of an increased risk of anastomotic stricture after application of acrylic adhesives, which can strongly influence therapeutic outcomes [55].…”
Section: Prevention Of Intestinal Anastomotic Leak -Current Methodsmentioning
confidence: 99%